RELATIONSHIP BETWEEN DURATION OF USING ANTIPSYCHOTICS DRUGS WITH CARIES STATUS ON SKIZOFRENIA PATIENTS IN SPECIAL HOSPITAL PROVINCE SOUTH SULAWESI, 2017 - DJAMALUDDIN, NURSYAMSI; ANWAR, AYUB IRMADANI; PASIGA, BURHANUDDIN DAENG; AKBAR, FUAD HUSAIN; PRATIWI, RINI; SAMAD, RASMIDAR; WULANSARI, DWI PUTRI; WARDHANI, YULIA (International Journal of Applied Pharmaceutics, 2019)
Objective: To provide an overview of the use of antipsychotic drugs with caries status in schizophrenic patients in Makassar. Methods: This was an analytic observational with cross-sectional study design. Sampling method was done with non-probability sampling with 74 samples. This research was conducted at the Regional Special Hospital of South Sulawesi Province on 19-23 April 2017. The data is presented in a table and analyzed by Spearman’s correlation test. Results: The study showed that the distribution of the average value of DMF-T in each sex group, age, and the duration of medicine use with 8.61±5.51. There is a significant relationship between the duration of antipsychotic medicine use and dental caries status and is also found r-value at 0.359 which denotes a positive correlation. Conclusion: There is a relationship between the duration of using antipsychotic drugs with dental caries status of schizophrenic patients as a result of the side effects of antipsychotic drugs.